Prevalence and Characteristics Associated with Breastfeeding Initiation Among Canadian Inuit from the 2007–2008 Nunavut Inuit Child Health Survey - McIsaac, Kathryn E.; Sellen, Daniel W.; Lou, Wendy; Young, T. Kue (2015)
"We aimed to determine the prevalence of, and factors associated with, breastfeeding initiation in Canadian Inuit. We used data from the Nunavut Inuit Child Health Survey, a population-based, cross-sectional survey conducted in the Canadian territory of Nunavut. Inuit children aged 3–5 years in 2007 or 2008 were randomly selected for the survey. Select household, maternal, infant and community characteristics were collected from the child’s primary caregiver and entered into logistic regression models as potential predictors of breastfeeding initiation. Analyses were repeated in a subgroup of caregiver reports from biological mothers." (as cited in abstract)